AFSONDERLIKE KERKE VIR AFSONDERLIKE BEVOLKINGSGROEPE? ENKELE OPMERKINGS OOR DIE SENDINGBELEID VAN DIE NEDERDUITS GEREFORMEERDE KERK - Jonker, W. D. (Scriptura, 1986)
This is a comment on the request of Portuguese members of the Dutch Reformed Church to establish their own autonomous Church. While conceding that such a step would be in accordance with the standing missions policy of the DRC - separate Churches for different population groups - the author argues that this should not be done at this stage. He is convinced that neither the Holy Scipture, nor the traditional Reformed principles of Church polity favour separate Churches for different population groups. On the contrary, the communion of saints demands that local churches not only practice Christian fellowship amongst themselves, but also extend a structural bond of love to all bearing the name of Christ. The diversity amongst members of the Church of Christ should neither be ignored nor regarded as reason for dividing the Church into separate racial or cultural ecclesiastical institutions, jeopardising true Christian fellowship among all members of the Church. The author contends that, apart from non-theological factors which have influenced this development, the nineteenth century view of the Church exercised specific influences on the present missions policy of the DRC.